Carcass, Organ and Organoleptic Characteristics of Spent Layers Fed Bambara Nut Sievates - Ugwu, S.O.C.; Onyimonyi, A.E. (International Journal of Poultry Science, 2007)
The carcass, organ and organoleptic characteristics of spent layers fed Bambara nut sievates (BNS) were investigated. Ninety laying hens of the Brown Nera strain in their 9th week of lay were randomly assigned to five dietary treatment in which BNS were incorporated at levels of 0 (control), 5, 10, 15 and 20 percent. There were eighteen birds per treatment and each treatment was replicated thrice in a Completely Randomized Design. The feeding trial lasted for 45 weeks during which each bird received 120g of feed/day. Results showed that final body weight, dressing percentage and residual weight were significantly affected by treatments (P